An isolated chemolithoautotrophic ecosystem deduced from environmental isotopes: Ayyalon cave (Israel) - Frumkin, Amos; Chipman, Ariel D.; Naaman, Israel (Frontiers in Ecology and Evolution, 2023)
The stable isotopes composition of chemolithoautotrophic cave ecosystems is known to differ from epigenic caves. Here we show that in addition, dead carbon (devoid of 14C), is utilized and transferred throughout this ecosystem, rendering it unsuitable for radiocarbon dating. The connectivity of the Ayyalon Cave ecosystem with the surface is studied, along with its sources of energy and carbon, as well as the interconnections between its constituents. We use isotopic evidence to show that its ancient resilient ecosystem is based on an underground food web depending on rich biomass production by chemolithoautotrophic nutrient supplies, detached from surface photosynthesis. Carbon isotopic values indicate that: (1) the microbial biota use bicarbonate from the groundwater (23.34 pMC [% of modern carbon]) rather than the atmospheric CO2 above the water (71.36 pMC); (2) the depleted 14C signal is transferred through the entire ecosystem, indicating that the ecosystem is well-adapted and based on the cave biofilm which is in turn based on groundwater-dissolved inorganic carbon. Incubation of Ayyalon biofilm with 14C-labelled bicarbonate indicates uptake of the radio-labeled bicarbonate by sulfur-oxidizing proteobacteria Beggiatoa, suggesting that these sulfur-oxidizing microorganisms use the water-dissolved inorganic carbon for chemolithoautotrophic carbon fixation. Organic matter in the cave is much lighter in its stable nitrogen and carbon isotopes compared with respective surface values, as expected in chemolithoautotrophic systems. This evidence may be applicative to subsurface voids of ancient Earth environments and extraterrestrial systems.